Serum Epidermal Growth Factor is Low in Schizophrenia and Not Affected by Antipsychotics Alone or Combined With Electroconvulsive Therapy - Zhang, Xiaobin; Xiao, Wenhuan; Chen, KuanYu; Zhao, Yaqin; Ye, Fei; Tang, Xiaowei; Du, Xiangdong (Frontiers in Psychiatry, 2020)
Background: Epidermal growth factor (EGF) is implicated in the pathogenesis of schizophrenia, suggesting possible value as a biomarker for disease severity or treatment response. However, basal EGF levels and changes during treatment are inconsistent across studies. The goal of this study is to compare serum EGF in schizophrenia patients before and after treatment with antipsychotics alone or combined with electroconvulsive therapy (ECT). Method: Patients meeting DSM-IV diagnostic criteria for schizophrenia were recruited from June 2013 to December 2015 (n=186) and followed-up after 8 weeks of treatment with antipsychotics alone (n = 119, drug group) or combined with ECT (n = 67, ECT group). Serum EGF levels were measured by ELISA and compared among patients and 74 healthy control subjects. Psychopathology and clinical effects were assessed using the Positive and Negative Syndrome Scale (PANSS). Results: Basal serum EGF was significantly lower in the entire patient cohort compared to healthy controls (P < 0.05). Repeated-measures ANOVA showed no main effect of time (F = 1.273; P = 0.261), time × group interaction (F =1.228; P =0.270), main effect of clinical response (F = 0.191; P = 0.663), or group × clinical interaction (F = 1.765; P = 0.186) on serum EGF. Serum EGF levels did not change significantly following antipsychotic drug or combined therapy (P > 0.05). Additionally, neither basal EGF nor EGF change was associated with the clinical response to drug or combined treatment (P > 0.05). However, Baseline serum EGF was weakly associated with PANSS positive score (pre-treatment: r = 0.206, post-treatment: r = 0.201) and general symptom score (pre: r = -0.244). Conclusions: Serum EGF concentration is low in schizophrenia but is unchanged following treatment with antipsychotics alone or combined with ECT, regardless of clinical response. Thus, serum EGF is not a surrogate biomarker for treatment response and is unlikely to be involved in the therapeutic mechanisms of antipsychotics or ECT.